ON SPATIAL LANDSCAPE PLANNING OF STAVROPOL REGION AND FEATURES OF SOILS RESOURCES - Oksana Aleksandrovna Bunina; Olga Gennadievna Bondareva (Вестник Северо-Кавказского федерального университета)
This article considers original aspects of territorial environmental planning of Stavropol region, formu- lation approach to specialized techniques of regional planning for territorial development of Stavropol region.